Telecommunications: Restructuring Work and Employment Relations World-Wide - Wagar, Terry H. (Relations industrielles / Industrial Relations, 1998)
The article reviews the book, "Telecommunications: Restructuring Work and Employment Relations Worldwide," edited by Harry C. Katz.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; Organizational change; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Telecommunications industry